(untitled) (Italian Journal of Public Health, 2006)
Background: The health status of a population sample living in Parona (Pavia) was surveyed to evaluate the association between exposure to active and passive smoke and chronic respiratory symptoms. Methods: 483 subjects were studied. The protocol included a questionnaire administrated by a physician, pulmonary function test and blood analysis. Results: 124 subjects were current smokers, 104 subjects were past smokers and 252 were non-smokers. Sixty two (12.9%) of the subjects had pathological PFT: 48 (10%) had airflow obstruction and 14 (2.9%) had restriction of lung volumes. The prevalence of pathological tests was significantly higher in males than in females (p < 0.05). Most of pathological tests have been found in smokers: the prevalence was 16.9% in current smokers, 14.4% in quitters, 11.8% in ETS-exposed people and 9.4% in ETS-non-exposed. The frequency of pathological PFTs was significantly higher in subjects exposed (p< 0.05). The mean value of FVC% predicted tended to be lower in smokers, intermediate in ETS exposed subjects. Conclusions: Chronic respiratory symptoms were reported significantly more often by smokers. The prevalence of pathological pulmonary function tests was significantly higher and FVC tended to be lower in subjects exposed to active and/or passive smoking than in non-exposed. Our results demonstrate the health impact of smoke on the general population of a low polluted area. Besides smoking cessation, lowering ETS exposure could represent one of the most important tool to improve respiratory health, and may contribute to prevent and reduce progression to COPD .